Foundation species across a latitudinal gradient in China. Issue 2 (30th November 2020) - Qiao, Xiujuan; Zhang, Jiaxin; Wang, Zhong; Xu, Yaozhan; Zhou, Tianyang; Mi, Xiangcheng; Cao, Min; Ye, Wanhui; Jin, Guangze; Hao, Zhanqing; Wang, Xugao; Wang, Xihua; et al.
Abstract: Foundation species structure forest communities and ecosystems but are difficult to identify without long‐term observations or experiments. We used statistical criteria––outliers from size‐frequency distributions and scale‐dependent negative effects on alpha diversity and positive effects on beta diversity––to identify candidate foundation woody plant species in 12 large forest‐dynamics plots spanning 26 degrees of latitude in China. We used these data (1) to identify candidate foundation species in Chinese forests, (2) to test the hypothesis––based on observations of a midlatitude peak in functional trait diversity and high local species richness but few numerically dominant species in tropical forests––that foundation woody plant species are more frequent in temperate than tropical or boreal forests, and (3) to compare these results with data from the Americas to suggest candidate foundation genera in northern hemisphere forests. Using the most stringent criteria, only two species of Acer, the canopy tree Acer ukurunduense and the shrubby treelet Acer barbinerve, were identified in temperate plots as candidate foundation species. Using more relaxed criteria, we identified four times more candidate foundation species in temperate plots (including species of Acer, Pinus, Juglans, Padus, Tilia, Fraxinus, Prunus, Taxus, Ulmus, and Corlyus ) than in (sub)tropical plots (the treelets or shrubs Aporosa yunnanensis, Ficus hispida, Brassaiopsis glomerulata, and Orophea laui ). Species diversity of co‐occurring woody species was negatively associated with basal area of candidate foundation species more frequently at 5‐ and 10‐m spatial grains (scale) than at a 20‐m grain. Conversely, Bray‐Curtis dissimilarity was positively associated with basal area of candidate foundation species more frequently at 5‐m than at 10‐ or 20‐m grains. Both stringent and relaxed criteria supported the hypothesis that foundation species are more common in mid‐latitude temperate forests. Comparisons of candidate foundation species in Chinese and North American forests suggest that Acer be investigated further as a foundation tree genus.